The association of non-severe COVID-19 infection and progression to frailty among robust older veterans - Natasha M. Resendes; Jerry Bradley; Fei Tang; Iriana S. Hammel; Jorge G. Ruiz (Elsevier, 2024)
Background: Studies have shown that frailty was increased in hospitalized COVID-19 patients. However, it is not clear whether non-severe COVID-19 increases the risk for pre-frailty and frailty development. Our study aimed to determine the risk of developing frailty and pre-frailty in robust veterans who contracted non-severe COVID-19. Methods: We conducted a retrospective cohort study to assess the association of SARS-CoV-2 infection with the development of pre-frailty and frailty status among robust U.S. veterans using VA COVID-19 Shared Data Resource. We included patients 55 years and older who had at least one SARS-CoV-2 testing between March 15, 2020, and November 30, 2020, had been active patients in the past 12 months, and had a VA frailty index of zero (robust status) at the time of testing. Cox proportional hazard model was used to assess the association between COVID-19 infection and developing frailty or pre-frailty and frailty. We also assessed the association by patients' age groups, sex, and race. Findings: We identified 82070 veterans mean age 68.3 ± 7.8, 74738 (91.1%) male, 53899 (65.7%) white, 7557 (9.2%) with mild COVID-19 infection. Over the follow up period of 36 months, testing positive for COVID-19 was associated with a 66% increase in the hazard of becoming frail (adjusted HR = 1.66, 95%CI: 1.32-2.08), and a 68% increase in the hazard of becoming pre-frail (adjusted HR = 1.68, 95%CI: 1.45-1.94). Among male patients, mild COVID-19 infection was associated with a 54% increase in the hazard of becoming frail (adjusted HR = 1.54, 95% CI: 1.21−1.96), while among female patients there was a 330% increase (adjusted HR = 4.30, 95% CI: 2.13−8.64). Conclusions and relevance: Non-severe COVID-19 infection that occurred in robust older adults increased the risk of developing frailty. Further multi-center prospective cohort studies evaluating the mechanism of action and clinical trials of treatment options for post-COVID frailty are indicated in Veterans to support clinical care.